Trends in insect biodiversity in a changing world - Ameixa, Olga Maria Correia Chita (Jihočeská univerzita, 2011)
In this thesis I investigated various factors that might affect species diversity and the relations between predator/parasitoid and host, using mainly insects as a model group. These factors were agricultural practices, landscape composition, climate change and invasive species.
Trends in insect biodiversity in a changing world
Keywords: Biodiversity; insects; agricultural practices; climate change; invasive species; landscape composition; Biodiversity; insects; agricultural practices; climate change; invasive species; landscape composition